2007
DOI: 10.1021/ja069131b
|View full text |Cite
|
Sign up to set email alerts
|

Photochromism of Diarylethene Single Molecules in Polymer Matrices

Abstract: Robust fluorescent photoswitching molecules, having perylene bisimide as the fluorescent unit and diarylethene as the switching unit, were prepared, and their photochromic reactions were measured at the single-molecule level in various polymer matrices. The histograms of the fluorescent on and off times were found to deviate from normal exponential distribution and showed a peak when the molecules are embedded in rigid polymer matrices, such as Zeonex or poly(methyl methacrylate) (PMMA). In soft polymer matric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
104
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 49 publications
5
104
0
2
Order By: Relevance
“…The observed irreversibility could be the result of a strong association of DAE_Me (closed form) with the network of BTBT crystallites, thereby suppressing photoswitching of DAE_Me back into its open form. Similar phenomena have been observed previously where it was shown that the photochromism of DAEs is strongly dependent on their environment and arrangement in the solid [20][21][22] . An alternative explanation may be given considering the photochemically induced degradation of the DAEs, which on prolonged ultraviolet irradiation forms a by-product 23 (see below).…”
Section: Resultssupporting
confidence: 89%
“…The observed irreversibility could be the result of a strong association of DAE_Me (closed form) with the network of BTBT crystallites, thereby suppressing photoswitching of DAE_Me back into its open form. Similar phenomena have been observed previously where it was shown that the photochromism of DAEs is strongly dependent on their environment and arrangement in the solid [20][21][22] . An alternative explanation may be given considering the photochemically induced degradation of the DAEs, which on prolonged ultraviolet irradiation forms a by-product 23 (see below).…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, photochromic compounds establish a synthetic approach to design and develop efficient photoswitches. Photochromic materials have attracted considerable interest in the last decades as optoaddressable rewritable memory devices and reversible photoswitches [67][68][69][70][71][118][119][120][121][122][123]. Photochromism is defined as a reversible transformation of a molecule induced in one or both directions by absorption of electromagnetic radiation between two forms exhibiting different absorption spectra [124,125].…”
Section: Photochromic Conjugatesmentioning
confidence: 99%
“…Embedded in the hydrophobic cavities of water-soluble nanoparticles the mero form shows strong fluorescence with a maximum around 670 nm and a fluorescence quantum yield of 0.18 [137,138]. On the other hand, photochromic compounds can be used advantageously as fluorescence resonance energy transfer (FRET) acceptors to reversibly switch the fluorescence of a donor fluorophore [70,71,122,123,[137][138][139][140][141]. Switching of the donor fluorophore is performed by modulating the absorption properties of the photochromic compound (Fig.…”
Section: Photochromic Conjugatesmentioning
confidence: 99%
“…Although the single-molecule approach provides detailed information about the properties and mechanisms, only a few examples of fluorescent switches have been demonstrated (4,5). Among the fluorescent switches, there are systems that use 2 different wavelengths for switching (photoswitchable molecules) (6)(7)(8)(9)(10)(11)(12)(13), those that switch the efficiency of photoinduced electron transfer (14,15) and those that respond to pH changes (15,16).…”
mentioning
confidence: 99%